TEACHING WRITING A DESCRIPTIVE TEXT BY USING ENVIRONMENTAL OBSERVATION STRATEGY - Reszy Yuli Harmenita; Yuli Tiarina (Universitas Negeri Padang, 2013)
The purpose of this article is to explain how the English teacher applies the Environmental Observation Strategy in teaching writing a descriptive text to Junior High School. The ability of Junior High School students in writing a descriptive text is weakness due to the use of strategy by the teacher is not interesting. Descriptive text is a genre of the text that illustrates and gives characteristics of a thing, an event and people including the behavior and identity of someone. One of teaching strategy, which helps students in writing descriptive text, is Environmental Observation Strategy. Environmental Observation Strategy is started by divided students in groups that is consisted by five students. Then they will observe the topic given from the teacher before, which is a group have to make idea while the observation happened. The time given is 10-15 minutes. After that, all of the idea of each group complete, so the groups combine the idea into a descriptive text. The implementing of Environmental Observation Strategy is hoped that it can be an alternative way to increase the ability of the students of Junior High School in writing. AbstrakTujuan penulisan artikel ini adalah untuk menjelaskan bagaimana cara menggunakan Environmental Observation Strategy. Kemampuan siswa SMP dalam memahami deskriptif teks masih sangat kurang disebabkan karena penggunaan media yang tidak menarik oleh guru dalam pengajaran. Deskriptif teks adalah suatu jenis teks yang berisikan gambaran atau ciri-ciri dari suatu benda, kejadian dan orang termasuk juga sifat dan tingkah laku seseorang. Salah satu media pengajaran yang dapat membantu siswa dalam memahami deskriptif teks adalah Environmental Observation Strategy Pengajaran menulis dengan menggunakan strategi Environmental Observation Strategy terlebih dahulu dimulai dengan membagi siswa dalam kelompok yang beranggotakan lima orang. Kemudian mereka akan mengobservasi topik yang telah diberikan guru sebelumnya dimana masing- masing anggota dalam kelompok harus membuat ide atau gagasan yang mereka dapat selama melakukan observasi tersebut. Waktu yang diberikan guru berkisar 10-15 menit. Setelah semua ide dari masing – masing anggota kelompok didapat, maka kelompok tersebut akan menuangkan ide tersebut dalam bentuk deskriptif teks. Penerapan Environmental Observation Strategy diharapkan bisa meningkatkan kemampuan dan motivasi belajar siswa, terutama dalam bidang menulis.